2010
DOI: 10.1039/c0cc03263h
|View full text |Cite
|
Sign up to set email alerts
|

meso-Alkylidene (m-benzi)pentaphyrin: a modified pentaphyrin bearing exocyclic double bonds at meso-positions

Abstract: meso-Alkylidene (m-benzi)pentaphyrin containing exocyclic C=C double bonds at two meso-positions is synthesized and fully characterized for the first time. The single crystal X-ray crystallographic analysis shows a concave conformation with two pyrrole rings inverted. The first protonation occurs exclusively at core nitrogen. The synthesized compound displays concentration dependent chromogenic responses for fluoride anion in organic solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 25 publications
2
22
0
2
Order By: Relevance
“…Subsequent oxidation with DDQ and purification by column chromatography,f ollowed by recrystallization from chloroform/methanol, afforded the desired pentaphyrin 1 in 8% yield. [16] The process has also resulted in the formationo fp artially oxidized form of dipyrihexaphyrini n 2% yield which is further oxidized by DDQ in refluxing toluene to afford 2.B oth the synthesized compounds are not expected to exhibit macroaromatic properties. Similar to m-benziporphyrins bearing meso-alkylidene,s ubstituent 2,6-pyriporphyrins 1 and 2 also exists in as ingle tautomeric form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent oxidation with DDQ and purification by column chromatography,f ollowed by recrystallization from chloroform/methanol, afforded the desired pentaphyrin 1 in 8% yield. [16] The process has also resulted in the formationo fp artially oxidized form of dipyrihexaphyrini n 2% yield which is further oxidized by DDQ in refluxing toluene to afford 2.B oth the synthesized compounds are not expected to exhibit macroaromatic properties. Similar to m-benziporphyrins bearing meso-alkylidene,s ubstituent 2,6-pyriporphyrins 1 and 2 also exists in as ingle tautomeric form.…”
Section: Resultsmentioning
confidence: 99%
“…[15] As part of our con-tinuinge fforts for the development of new porphyrin analoguesb earing exocyclic double bonds at multiple meso-positions, we here report the syntheses and chemical properties of new meso-diethylmalonylidene-2,6-pyriporphyrins 1 and 2.T he observations made in these studies showed that the pyriporphyrinoids do not possess porphyrin-like, global-aromatic character.T hese unusual properties based on our previous report have inspiredu st of urther exploret he anion-sensing properties of the pyriporphyrinoid 1. [16]…”
Section: Introductionmentioning
confidence: 99%
“…Molekülstrukturen von Dibenzocarbaamethyrin( oben) und dessen Bis-Zink(II)-Komplex (unten) gemäßRçntgenstrukturanalyse. Angewandte Chemie in Bezug auf die durchschnittliche makrocyclische Ebene einzunehmen (Abbildung 6).Außer der Synthese des Dithia-m-benzisapphyrins 93 gelang Lee und Mitarbeitern auch die von m-Benzipentaphyrin(1.1.1.1.1) 94 (Schema 17) [98]. Der Makrocyclus wurde als eines der Produkte isoliert, die im Verlauf der säureka-talysierten Kondensation von m-Benzitripyrran mit Pyrrol und Perfluorbenzaldehyd und der anschließenden Neutralisation und DDQ-Oxidation erhalten wurden.…”
unclassified
“…[8] Recently,aseries of expanded benziporphyrinoids have been reported by incorporating one or more benzene units with distinct bonding (mainlyo fm and p)m ode into the macrocyclic core. [13][14][15][16][17] These contributions were mainly focusedo na romatic characteristics, but their coordination chemistry is scarcely reported. [8,[13][14][15][16][17] It is also important to note that porphyrin analogues with terphenyl moieties embedded in the macrocycle structure have not been explored so far.S uch macrocyclesw ith distinct bonding mode can provide multiple coordination sites in the macrocyclic framework.…”
mentioning
confidence: 99%
“…[13][14][15][16][17] These contributions were mainly focusedo na romatic characteristics, but their coordination chemistry is scarcely reported. [8,[13][14][15][16][17] It is also important to note that porphyrin analogues with terphenyl moieties embedded in the macrocycle structure have not been explored so far.S uch macrocyclesw ith distinct bonding mode can provide multiple coordination sites in the macrocyclic framework. In the presents tudy,w ec ollectively describedt wo unexplored topics, such as incorporation of the terphenylene unit into the porphyrin core, and carba-analogues of homoporphyrins.…”
mentioning
confidence: 99%